Cardiac Sarcoidosis Managed by Biventricular Pacing: A Case Report - Khoury, Samih; Bechara, Tony; Dabbous, Mohammed; Saba, Micheal; El Orra, Said (International Journal of Clinical Research, 2022)
Background: Cardiac sarcoidosis (CS) is a rare pathology that affects the middle-aged population. Its diagnosis, as well as its treatment, can be quite challenging, especially dealing with device management. We hereby discuss a case of CS, managed by a biventricular pacemaker in a 43-year-old man. Case Report: A 43-year-old male presented to the emergency department with a 15-day history of chronic cough and worsening dyspnea. On examination, he was found to be bradycardic in the context of a third-degree heart block on ECG as well as bilateral hilar lymphadenopathy on chest radiography. Based on these findings, cardiac sarcoidosis was suspected. A temporary right internal jugular transvenous pacemaker was implanted in the right ventricle and empiric corticosteroid management was commenced. Lung tissue biopsies were obtained via bronchoscopy and were positive for granulomas consistent with a diagnosis of sarcoidosis. Even though the patient showed a partial positive response to corticosteroid treatment, he required a permanent pacemaker. A dual-chamber implantable cardioverter-defibrillator (ICD) was implanted and the patient was discharged on prednisone. His follow-up plan consisted of serial echocardiography and consideration of a new coronary sinus lead in the event of left ventricular dysfunction in the future. Conclusion: Cardiac rhythm management in the context of CS is often difficult, with decisions that need to be made between a pacemaker, a defibrillator, or a cardiac resynchronization device. The idea that biventricular pacing has a preventative role against heart failure in patients with normal left ventricular ejection fraction and CS deserves more attention and discussion.